Microcomputer controlled robotic arm / Hassan Alias - Alias, Hassan (1984)
The microcomputer controlled robotic arm in designed to have a five degree of freedom and of a small scale size. It has an articulated arm jointed at shoulder, elbow and wrist positions. Both the upper and lower arms rotate about the base and there is a motor driven gripper. The entire robotic system can be divided into three main parts namely the controlling computer, interface board and the robot itself which is made up of mechanical parts. The interface board is designed, base on memory mapped peripheral of the controlling computer, that is the robotic motors are treated as memory locations instead of input/output ports. Each of the arm movement is servo controlled, which mean, there is a position sensor feeding back information to the interface board, where it is compared with the programmed position and automatically taking corrective action. Since the serve action is independent of the host computer, it greatly simplifying the software design to drive the robot. This interface also employed a parallel bit data transfer from the data bus to the interface circuitory. All the five axes are driven by a motor with an integral gearbox. For the wrist and gripper, small in-line gearboxes are used. The other axes namely shoulder, elbow and the base utilised a more powerful gearboxes. The motors require a 12V DC supply.